Optimal choice of prophylactic anticoagulant therapy for nonvalvular atrial fibrillation in the context of COVID-19 pandemic - A. S. Polyakov; V. V. Tyrenko; E. V. Kryukov; Ya. A. Noskov (Российский кардиологический журнал, 2021)
Already at the very beginning of COVID-19 pandemic, it became known about the key clinical and pathogenetic significance of immunopathological reactions and disorders of hemostasis. Specific coagulopathy, microvascular thromboinflammatory organ damage, macrothrombosis and thromboembolism in the acute period of COVID-19, as well as secondary hemostasis disorders in convalescents, actualize the issues of caring patients with cardiovascular disease. COVID-19 not only increases the risk of thromboembolic events for patients with previously identified arrhythmias, but can also indirectly cause it (as a complication of infection or therapy). The aim of this work was to summarize the data and substantiate the optimal choice of prophylactic anticoagulant therapy for nonvalvular atrial fibrillation during the COVID-19 pandemic. Atrial fibrillation is not only the most common type of supraventricular tachyarrhythmia, but it is also the main underlying cause of more than half of cardioembolic stroke cases, which requires effective thromboprophylaxis. While maintaining the infectious danger for patients, the anticoagulant selection should take into account the possible dysfunctions and drug interactions during the initial infection or reinfection of COVID-19, as well as the possibility of rapid anticoagulant action reverse if surgery is required or bleeding develops. The optimal choice seems to be the use of dabigatran, which is characterized by the best safety profile for hepato- and nephrotoxicity, cytochrome P450-independent metabolism, and the presence of an antidote.